A cross-sectional study on workplace experience: a survey of nurses in Quebec, Canada - Marie-Annick Gagné; Carl-Ardy Dubois; Alexandre Prud'Homme; Roxane Borgès Da Silva (BMC, 2019)
Abstract Background Nurses play a significant role in healthcare systems. Their workplace experience can have an impact not only on nurses themselves, but also on patients and organizations, particularly in terms of quality of care and performance. Despite the importance of this experience, it remains an ambiguous concept with varying interpretations. Current studies do not fully capture its complexity, as its multiple dimensions are often considered in isolation. As such, developing a portrait of nurses' workplace experience that integrates its multiple dimensions can provide decision-makers with better indications regarding what levers can be mobilized to generate positive results for nurses, patients, and organizations. Aim To identify profiles of nurses' workplace experience in Quebec, Canada. Design Cross sectional. Methods In April 2017, 891 nurses participated in this study by completing a self-administered questionnaire. Four dimensions of nurses' workplace experience were measured: resources available to them in their workplace, personal resources, demands (psychological and physical) placed on them, and outcomes associated with their work. Descriptive and factorial analyses were performed. Results Three profiles of nurses' workplace experience emerged from the factorial analyses: nurses in distress, nurses in moderately positive situations, and nurses in positive situations. Conclusion The study identified profiles of nurses' workplace experience that were differentiated based on nurses' access to workplace resources, the demands of their work, and outcomes. Healthcare managers can use the results to improve the quality of nurses' workplace experience by improving access to structural work resources and alleviating psychological demands.